2019
DOI: 10.1126/sciadv.aav5003
|View full text |Cite
|
Sign up to set email alerts
|

Carbon doping of WS 2 monolayers: Bandgap reduction and p-type doping transport

Abstract: Chemical doping constitutes an effective route to alter the electronic, chemical, and optical properties of two-dimensional transition metal dichalcogenides (2D-TMDs). We used a plasma-assisted method to introduce carbon-hydrogen (CH) units into WS2 monolayers. We found CH-groups to be the most stable dopant to introduce carbon into WS2, which led to a reduction of the optical bandgap from 1.98 to 1.83 eV, as revealed by photoluminescence spectroscopy. Aberration corrected high-resolution scanning transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
154
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(162 citation statements)
references
References 41 publications
8
154
0
Order By: Relevance
“…Other nonmetal dopants such as B, Cl, Se, and C have also been investigated. [ 95,97,111,119 ] They can either tune the electronic structure to improve the electronic transport or tune the Δ G H* for a better HER, i.e., the Δ G H* of −0.05 eV at the plane B site of the B doped MoSe 2 sheet and the highly improved catalysis of the Cl doped MoS 2 . [ 95,111 ] With the same principle, using alternating layers of different chalcogen atoms within a single mono‐layer TMD can also improve HER performance.…”
Section: Progress On Strategies To Improve the Her Catalytic Activitymentioning
confidence: 99%
“…Other nonmetal dopants such as B, Cl, Se, and C have also been investigated. [ 95,97,111,119 ] They can either tune the electronic structure to improve the electronic transport or tune the Δ G H* for a better HER, i.e., the Δ G H* of −0.05 eV at the plane B site of the B doped MoSe 2 sheet and the highly improved catalysis of the Cl doped MoS 2 . [ 95,111 ] With the same principle, using alternating layers of different chalcogen atoms within a single mono‐layer TMD can also improve HER performance.…”
Section: Progress On Strategies To Improve the Her Catalytic Activitymentioning
confidence: 99%
“…The band gap of pristine monolayer WS2 is direct and about 1.80 eV, which agrees well with the literature. [21] The existence of V1S results in the generation of defect states at the band gap regions (as shown in Figure 4, b-e).…”
Section: Resultsmentioning
confidence: 99%
“…al demonstrated that p-type doping of MoS2 is attained by substitutional nitrogen doping. [20] Furthermore, various reports have shown that p-type doping behavior can also be obtained by introducing carbon to monolayers of WS2 [21] , phosphorus to MoS2 [22] and oxygen adsorption to MoS2 [23] . However, these doping methods pose major concerns in terms of crystal stability, impurity, and structural damage (or even etching) by energetic ions, particularly for monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, a transistor made of a bi-layer graphene nanoribbon with a band gap of~0.16 eV shows a dramatically boosted on-off ratio of 10 711 . Besides the thickness control in this example, the band gap engineering of 2D materials has been widely explored by a number of chemical methods such as covalently bonding or physically adsorbing organic functional molecules, doping heteroatoms or alloying the second 2D materials into the primitive 2D semiconducting materials 10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Among these methods, organic modification onto 2D materials by covalently bonding or physically adsorbing organic molecules not only possess the ability to modulate the band gap, but also to introduce functions related to organic molecule into 2D materials, such as better dispersion in solvent, extra light absorption and favorable affinity for target chemicals 4,15,[32][33][34] .…”
mentioning
confidence: 99%
“…1a). The maximum modulated scope on the band gap by organic modification methods to date has been limited to 0.15 eV to date 15 . Secondarily, the organic groups on 2D materials are not homogeneously distributed, and this hinders the application of these materials.…”
mentioning
confidence: 99%